Exploring the potential for mergers and strategic partnerships within the Australian higher education system through the application of Value Nets. Issue 4 (3rd July 2020) - Harkin, Damien G.; Goedegebuure, Leo
ABSTRACT: We apply Value Nets as a tool for identifying potential partnership opportunities between the University of Adelaide (UofA) and University of South Australia (UniSA), and between the University of Queensland (UQ) paired with the Queensland University of Technology (QUT). Institutional profile data revealed a similar relationship within each pair. UQ and UofA are local pacesetters in research and offer a comprehensive range of courses. QUT and UniSA have developed world-class research programs and generally outperform their older neighbour in learning and teaching. The research performance gap between UofA and UniSA is narrower than that seen between UQ and QUT. Value Nets provide a useful tool for deeper reflection. The case for merger is stronger for UofA and UniSA. Nevertheless, a closer examination reveals significant potential for divergent opinions about how such a merger should be implemented. More importantly, Value Nets reveal significant opportunities for mutual gain without the requirement for merging.